A relationship between the surface composition and spectroscopic properties of cesium lead bromide (CsPbBr3) perovskite nanocrystals: focusing on photoluminescence efficiency. Issue 3 (20th December 2019) - Park, Jumi; Kim, Youngsik; Ham, Sujin; Woo, Ju Young; Kim, Taehee; Jeong, Sohee; Kim, Dongho
Abstract : This work explored the role of ZnBr2 in the surface composition and photoluminescence stability of CsPbBr3 nanocrystals. Abstract : We have previously developed CsPbBr3 NCs exhibiting a tremendously high photoluminescence (PL) and structural stability by adding ZnBr2 . However, understanding of these outstanding properties is lacking due to the absence of spectroscopic analyses, such as spectral or dynamical characteristics. In this work, we conducted a comparative analysis of photophysical properties for conventional-CsPbBr3 NCs and ZnBr2 –CsPbBr3 NCs. First, we analyzed the blinking traces by comparing the single crystal PL intermittency. It has been found that the PL quantum yield of CsPbBr3 NCs is gradually decreasing at the ensemble level, resulting from a significant activation of the Auger-induced blinking. Furthermore, the time-resolved TA dynamics supports the fact that Auger-type energy transfer accelerates the hot carrier cooling time, and thereby the Auger-induced blinking behavior in the band-edge state becomes dominant over time. Here, ZnBr2 –CsPbBr3 NCs showed a low multiexciton Auger amplitude and therefore had a stable PL emission compared with conventional-CsPbBr3 NCs. Finally, we suggest that both NCs differ in intraband spacing possibly due to capping ligands, finally leading to a suppressed Auger process and higher stability for ZnBr2 –CsPbBr3 NCs.